Role of microRNA-129-5p in osteoblast differentiation from bone marrow mesenchymal stem cells - Xiao, W Z; Gu, X C; Hu, B; Liu, X W; Zi, Y; Li, M (Cellular and Molecular Biology, 2016)
Mesenchymal stem cells derived from bone marrow have the capacity to differentiate into osteoblast, chondrocyte, nerve cell and myocardial cell in vitro, which are an ideal engraft in tissue-engineered repair. Osteoblast differentiation is a vital process in maintaining bone homeostasis in which various transcriptional factors, including signaling molecules, and microRNAs (miRNAs). In this research, human bone marrow mesenchymal stem cells (hBMSCs) were induced differentiation into osteoblast in vitro after over-expression of miR-129-5p. The results showed that the hBMSCs could induce differentiation into osteoblast under the special condition medium, but when the miR-129-5p was over-expressed in hBMSCs, the differentiated efficiency and induced time of osteoblast from hBMSCs could be promoted. This reason was demonstrated that signal transducer and activator of transcription 1 (STAT1) was a transcriptional repressor of osteoblast gene (Runx 2) expression during osteoblast differentiation, miR-129-5p reduced STAT1 levels, leading to the accumulation of correctly spliced Runx 2 mRNA and a dramatic increase in Runx 2 protein.